Structural characterization and antioxidant activity of processed polysaccharides PCP-F1 from Polygonatum cyrtonema Hua. - Zhao, Yuanyuan; Wang, Zhen; Fu, Ranze; Xie, Ruonan; Wang, Bin; Li, Qinglin (Frontiers in Nutrition, 2023)
Polygonatum cyrtonema Hua. (PC) is a traditional Chinese herb with a history of use in both food and medicine. For clinical use, processed PC pieces are most commonly used, while present research has focused on crude PC polysaccharides (PCPs). In this study, a new polysaccharide, PCP-F1, with a molecular weight of 37.46 kDa, was separated from four-time processed PCPs by column chromatography and evaluated by antioxidant activity. It was composed of glucose, mannose, galactose, rhamnose, and galacturonic acid with a molar ratio of 3.5:2.5:1.3:1.8:0.8. The methylation analysis and two-dimensional NMR measurement revealed that the configuration of PCP-F1 contained nine residues in the primary structural unit by the chain of →3)-α-D-Glcp, →2)-α-D-Glcp(6→, →1)-ꞵ-D-Glcp(2→, →2)-α-D-GalAp(3,4→, →1) -ꞵ-D-Manp(3→, →2)-α-D-Glcp(3→, branched for →3)-α-D-Glcp, →2)-ꞵ-D-Galp(4→, →1)-ꞵ-D-Glcp(2→, →2,4)-α-D-Manp(6→, →3)-α-L-Rhap(4→. Radical scavenging assays indicated that PCP-F1 could scavenge radicals with a high scavenging rate, suggesting PCP-F1 possesses good antioxidant activity. The study confirms the importance of processed PC and offers the potential for exploiting it as a functional food.